Clinicopathological Characterization of Central Nervous System and Spinal Histiocytosis: A Three-Case Series Including Langerhans and Non-Langerhans Cell Subtypes - Ibrahim, Bilal; Arabyat, Abdallah; Y. Hiasat, Mohammad; F. Dabbas, Waleed (Journal of Neonatal Surgery, 2025)
Background: Histiocytic disorders of the central nervous system (CNS) and spine are rare and diagnostically complex, requiring integration of clinical, radiological, histopathological, and molecular data. Recent classifications emphasize molecular alterations, including ALK gene fusions, which define ALK-positive histiocytosis as a distinct, therapeutically actionable entity. Accurate subclassification is essential for effective treatment. Case Reports: We report three cases representing different CNS histiocytic subtypes. Case 1: A 27-year-old male presented with progressive lower limb weakness and radicular pain. MRI showed an intradural lesion initially suspected to be a schwannoma. Histopathology and immunohistochemistry confirmed ALK-positive histiocytosis, with KIF5B-ALK fusion detected by RT-PCR. Complete resection led to full neurological recovery with no recurrence at 4 years. Case 2: A 36-year-old male presented with headaches and focal seizures. Imaging revealed a dural-based lesion mimicking meningioma. Histopathology demonstrated Rosai-Dorfman disease with emperipolesis and an S100-positive, CD1a-negative immunophenotype. The patient remains disease-free at 2 years post-resection. Case 3: A 36-year-old male with vertebral Langerhans cell histiocytosis (LCH) presented with back pain and radiculopathy. Diagnosis was confirmed by CD1a and Langerin positivity; BRAF V600E mutation testing was negative. Conclusions: This series highlights the diagnostic challenges of CNS histiocytic disorders and underscores the value of comprehensive histopathological, immunohistochemical, and molecular profiling. Subclassification facilitates accurate diagnosis and guides individualized treatment, including the potential use of targeted therapies.